Association of change in brain structure to objectively measured physical activity and sedentary behavior in older adults: Age, Gene/Environment Susceptibility-Reykjavik Study - Arnardottir, Nanna Yr (Behav Brain Res, 2015)
Many studies have examined the hypothesis that greater participation in physical activity (PA) is associated with less brain atrophy. Here we examine, in a sub-sample (n = 352, mean age 79.1 years) of the Age, Gene/Environment Susceptibility-Reykjavik Study cohort, the association of the baseline and 5-year change in magnetic resonance imaging (MRI)-derived volumes of gray matter (GM) and white matter (WM) to active and sedentary behavior (SB) measured at the end of the 5-year period by a hip-worn accelerometer for seven consecutive days. More GM (β = 0.11; p = 0.044) and WM (β = 0.11; p = 0.030) at baseline was associated with more total physical activity (TPA). Also, when adjusting for baseline values, the 5-year change in GM (β = 0.14; p = 0.0037) and WM (β = 0.11; p = 0.030) was associated with TPA. The 5-year change in WM was associated with SB (β= −0.11; p = 0.0007). These data suggest that objectively measured PA and SB late in life are associated with current and prior cross-sectional measures of brain atrophy, and that change over time is associated with PA and SB in expected directions.